Pengaruh Temperatur, Komposisi Bahan Cangkang Inti Kelapa Sawit dan Konsentrasi Perekat pada Karakteristik Briket Komersial dari Tempurung Kelapa Sawit - Guna Bangun Persada; Putty Yunesti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Briquettes are an essential product for metal mineral processing plants in Indonesia. One good alternative raw materials for briquettes that do not pollute the environment is the palm kernel shell. This research was conducted by making briquettes from palm kernel shells to find optimal variations in carbonization temperature, material mixture, and adhesive mixture. The research was conducted on a laboratory scale. The palm kernel shell and coal kernel were carbonized at various temperatures, namely 450°C, 550°C, and 650°C, then crushed and sieved to 35 mesh. The powdered palm kernel shell and coal that have become powdered charcoal are weighted based on a mixture of powder and the adhesive composition ratio of 40 g. After that, the briquettes were formed under a pressure of 100 kg/cm² on a cylindrical mold with 40 mm. The analyzes carried out were moisture content, ash content, volatile substances content, fixed carbon content, calorific value, compressive strength, density, porosity, and SEM (Scanning Electron Microscope). The results showed that the briquette from the kernel of the palm kernel shell was optimal at a temperature of 550 ° C with a starch adhesive mixture of 7.5%, a pressure of 100 kg/cm², moisture content of 5.34%, an ash content of 5.81%, a substance content. Volatile amounted to 18.77%, 71.08% for fixed carbon, heating value 7125.86 cal/g. Density of 0.78, porosity of 0.04 and strength of 72.56 kg / cm².